Cytotoxic of Usnic Acid Isolated from Ramalina sp.: Cytotoxic of Usnic Acid Isolated from Ramalina sp. - Darmawan, Akhmad; Maulidiyah; Megawati; Ariani, Novita; Aisya, Sitti; Sukirno; Randy, Ahmad; Primahana, Gian; Hendra, Medi; Nurdin, Muhammad (Journal of Tropical Life Science, 2024)
Ramalina sp. (Ramalinaceae) is a type of lichen known to contain many active secondary metabolite compounds that have the potential to be used as medicine or medicinal raw materials. One of the biological activities possessed by Ramalina sp. lichen is its anticancer activity. This research aims to isolate and identify active secondary metabolite compounds from the methanol extract of the Ramalina sp. lichen and to find out the cytotoxic activity of the isolated compound against MCF7 breast cancer cells. Compound 1 (usnic acid) was successfully isolated from fraction A. The isolation and purification process was carried out starting with a maceration process using acetone solvent, followed by silica gel column chromatography using a gradient solvent system consisting of n-hexane, n-hexane:EtOAc, EtOAc, EtOAc:MeOH, and MeOH with 5% increment of polarity to obtain 17 fractions (F-1 to F-17). From the 17 fractions obtained, fraction 3 (F-3) and fraction 4 (F-4) (eluted with n-hexane:EtOAc 30%), which had the same TLC profile, were combined and named as fraction A. Compound 1 (50 mg) is a yellow needle crystal that was formed in a bottle of fraction A, which was obtained after the process of combining fractions F-3 and F-4 and solvent evaporation process. The crystals were then separated and purified with CHCl3 and MeOH. Compound 1 was then characterized based on spectroscopic data. Various spectroscopic analysis data, including FTIR, 1D- and 2D-NMR, and LC-ESI-MS, show that Compound 1 is a dibenzofuran derivative compound with 18 carbons (3 from carbonyl groups (C=O) and 3 from methyl groups) and 2 hydroxyl (-OH). Cytotoxicity assay showed that at a low concentration of 18.75 ug/mL, Compound 1 caused a 67.06% decrease in MCF7 viability